Answer:
40
Step-by-step explanation:
(2x+1/(2x))^5 *(2x -1/(2x))^5
= ((2x)^2 -1/(2x)^2)^5 (a+b)*(a-b) =a2-b2
= (4x^2-1/4(x)^2)^5
now
x =4x^2. ,a = 1/4(x)^2 ,n =5
we have
general term = Cr *x^r *a^(n-r)
= Cr * (4x^2)^r * (1/4(x)^2)^(n-r)
= Cr *4^r * X^2r * 1/( 4^(n-r) *x^(2n-2r)
= Cr * 4^r/4^(n-r) * x^(2r)/x^(2n-2r)
= Cr * 4(2r-n) *x(4r-2n)
now for x^2
4r-2n = 2
4r -10=2
4r =12
r = 3
now for coeff
C(5,3) * 4^(2*3-5)
5!/(3!*(5-3)!) * 4
5*4/(2*1)*4
40
Answer:
30cm, 60cm
Step-by-step explanation:
Given data
Dimensions of the first rectangle
Length =10cm
Width =20cm
We are told that the dimensions of the second rectangle is gotten by multiplying the first rectangle by 3
Hence the dimensions of the second rectangle is
Length =10*3= 30cm
Width = 20*3= 60cm
The answer is a I hope this helps your welcome
Answer:
a
Step-by-step explanation: